Answer:
The second term is -6 , the fourth term is 0 , the eleventh term is 21
Explanation:
* Lets revise the explicit formula
- An explicit formula will create a sequence using n, the number
position of each term.
- If you can find an explicit formula for a sequence, you will be able
to quickly and easily find any term in the sequence by replacing
n with the number of the term you want
- It defines the sequence as a formula in terms of n.
* Now lets solve the problem
- The formula of the sequence is A(n) = -9 + (n - 1)(3)
- A(n) is any term in the sequence
- n is the position of the number
- To find the second term put n = 2
∵ n = 2
∴ A(2) = -9 + (2 - 1)(3) = -9 + (1)(3) = -9 + 3 = -6
* The second term is -6
- To find the fourth term put n = 4
∵ n = 4
∴ A(4) = -9 + (4 - 1)(3) = -9 + (3)(3) = -9 + 9 = 0
* The fourth term is 0
- To find the eleventh term put n = 11
∵ n = 11
∴ A(11) = -9 + (11 - 1)(3) = -9 + (10)(3) = -9 + 30 = 21
* The eleventh term is 21